Bridging for Better Conservation Fit in Indonesia's Coastal-Marine Systems - Berdej, Samantha; Armitage, Derek (Frontiers in Marine Science, 2016)
Efforts to improve the fit between conservation initiatives (e.g., marine protected areas, no-take zones) and the dynamic social dimensions of coastal-marine systems remain underdeveloped. We empirically illustrate here how opportunities to enhance ‘conservation fit’ are influenced by bridging organizations that serve to (1) better align conservation initiatives with characteristics of the social context that influence conservation outcomes (e.g., institutions, culture, values, local practice), (2) foster coordinated and adaptive approaches to conservation that are reflective of multiple perspectives and knowledge, and (3) better connect people and conservation actions across jurisdictional and geographical boundaries. Qualitative methods were used in this research, including semi-structured interviews, observation of key events and meetings, and literature review. We draw from three coastal-marine conservation cases in Bali, Indonesia that exemplify different approaches to bridging for conservation fit: the Bali MPA Network, the Nusa Penida MPA, and the East Buleleng Conservation Zone. Our synthesis of these cases identifies different strategies used by bridging organizations to deal with conservation fit issues, including their capacity to integrate actors and perspectives using flexible approaches, actualize hybrid forms of decision-making, build capacity and leadership, and foster cross-scale conservation and scale-bridging social networks. We also examine the limitations of bridging organizations and offer direction for future research for coastal-marine conservation in Indonesia specifically, and the Coral Triangle region generally. More broadly, this analysis contributes new insights on emerging forms of governance designed to deliberatively fit conservation initiatives to coastal-marine social-ecological systems experiencing rapid change.